High‐temperature Raman spectroscopy of the Cs2O–B2O3–MoO3 system for CsB3O5 crystal growth. Issue 2 (1st March 2016) - Liu, Shanshan; Zhang, Guochun; Wan, Songming; You, Jinglin; Ammar, Mohamed-Ramzi; Canizarès, Aurélien; Simon, Patrick; Wu, Yicheng
Abstract : Raman spectroscopy at high temperature has been applied to study in situ the microstructure of the solution in a Cs2 O–B2 O3 –MoO3 growth system. The Raman spectra near the interface show that at the boundary an isomerization reaction from three‐ to four‐coordinated boron occurred. Abstract : Raman spectroscopy at high temperature has been applied to study in situ the microstructure of the solution in a Cs2 O–B2 O3 –MoO3 growth system. A crystal–solution interface was observed. The BO groups consist of spiral chains based on B3 O4 Ø2 rings in the solution (Ø is a bridging O atom). The Raman spectrum of the solution indicates that MoO4 tetrahedra existed in the growth system. The nonbridging O atoms of the chains combined with the MoO4 groups, which decreased the viscosity. The Raman spectra near the interface show that at the boundary an isomerization reaction from three‐ to four‐coordinated boron occurred. The formation of B3 Ø7 triborate groups occurred. The morphology of the CsB3 O5 crystal resulting from spontaneous crystallization was observed to correspond to our expectations.